An investigation of age-related changes in the brain and the neuroprotective effects of the omega-3 fatty acids docosapentaenoic acid and eicosapentaenoic acid - Kelly, Laura Catherine (Trinity College (Dublin, Ireland). Department of Physiology, 2009)
The data presented here indicate that the n-3 polyunsaturated fatty acid docosapentaenoic acid (DPA), a metabolite of eicosapentaenoic acid (bPA), possesses neuroprotective and anti-inflammatory properties. Previous evidence has shown that EPA can have a neuroprotective effect and has the ability to attenuate age- related changes. EPA has been demonstrated to prevent the age-related deficit in LTP, attenuate the age-related increase in interleukin (1L)-1(3 and can increase IL-4 levels, which are known to decline with age. The data presented in this study indicate that oral administration of DPA and EPA for a period of 8 weeks modulated changes induced by age in the rat cortex and hippocampus including the age-related impairment in long-term potentiation (LTP) in the hippocampus.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin